Political parties, globalization and labour strength: Assessing differences across welfare state programs - Engler, Fabian (European journal of political research, 2020)
This article investigates how globalization and organized labour condition partisan effects on different welfare state programs. The main argument is that the conditional effect of globalization on government partisanship depends on how relevant a program is to the needs of vulnerable groups and that organized labour additionally affects this relationship. Analyzing 21 OECD countries between 1980 and 2011/2014, empirical evidence largely corroborates this argument: Firstly, the expectation that partisan differences decrease with globalization in general and especially in weak labour countries in the case of programs that are less relevant for compensation holds true for old-age provision and partly for sick pay insurance. Secondly, and in accordance with theoretical expectations concerning programs that are primarily relevant for compensation, partisan differences increase with globalization, in general regarding education and only in strong labour countries regarding unemployment benefits. Therefore, while globalization constrains national politics’ room for manoeuvre in some areas, parties are still able to follow their ideologically preferred policies and respond to compensation demands in others.
Gesehen am 12.08.2021